Governing production, shaping legislation? Apparel and automotive sector governance and firm representation in European Commission Expert Groups - Signe Louise Moe (Südwind-Verlag, 2021)
The Master thesis of Ms. Signe Louise Moe with the title "Governing Production, Shaping Legislation? Apparel and Automotive Sector Governance and Firm Representation in European Commission Expert Groups" analyzes the interconnection between the economic power of firms' in global value chains (GVCs) and their political power, in particular with regard to their representation at the EU level. Given the large-scale geographic reorganization of production at the global level since the 1970s, which also had important effects on the economies of the Global South, GVC analysis has become a topical field of inquiry in development studies. However, the GVC literature has - for a long time - overlooked the role of the state and the interconnection between the state and the corporate sector. By way of linking the GVC framework with the strategic-relational approach (a concept taken from Critical Political Economy), Ms. Moe's thesis offers an innovative perspective on how and why the articulation of political power differs across GVCs, sectors and firms. In doing so, the thesis reveals the links between the governance of the automotive and apparel sector and their representation in the European Commission Expert Groups. Given the eminently important role of properly understanding corporate behavior and the relations between the corporate sector and governments, the novel approach applied in this study is of particular relevance for the forthcoming discussion on EU binding human rights due diligence legislation in GVCs.
Keywords: 330